2021
DOI: 10.5999/aps.2019.00311
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative near-infrared spectroscopy for pedicled perforator flaps: a possible tool for the early detection of vascular issues

Abstract: Background Pedicled perforator flaps can present postoperative complications similar to those encountered in free flap surgery. Beyond a clinical evaluation, there is still no reliable technical aid for the early prediction of vascular issues. The aim of this study was to assess the support of near-infrared spectroscopy technology as an intraoperative tool to anticipate postsurgical flap ischemia.Methods We prospectively enrolled 13 consecutive patients who were referred to our hospital from March 2017 to July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Flap coverage has shown efficacy and safety [15][16][17] in complex defect reconstruction, offering a more viable solution compared to the use of other products such as dermal matrices. 18 Although different studies are available in the literature reporting the efficacy of flap coverage in defects of the posterior trunk and spine, [19][20][21][22][23][24][25][26][27] they all report the coverage of defects that cannot be closed primarily.…”
Section: Discussionmentioning
confidence: 99%
“…Flap coverage has shown efficacy and safety [15][16][17] in complex defect reconstruction, offering a more viable solution compared to the use of other products such as dermal matrices. 18 Although different studies are available in the literature reporting the efficacy of flap coverage in defects of the posterior trunk and spine, [19][20][21][22][23][24][25][26][27] they all report the coverage of defects that cannot be closed primarily.…”
Section: Discussionmentioning
confidence: 99%
“…A perforator‐based propeller flap usually combines the advantages of pedicled local flaps (good tissue match), pedicled regional flaps (180° arc of rotation), pedicled distant flaps (reliable), and free flaps (tissue away from zone of injury) (Marchesi, Amendola, et al, 2021; Marchesi, Garieri, et al, 2021; Xu et al, 2022). Ulnar perforators can be located proximally to RFFF donor site; consequently, the skin paddle is harvested from the proximal‐middle third of the forearm and its donor site can be easily managed without tendon exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck reconstruction, monitoring of free flaps is performed at 1-hour intervals on postoperative day (POD) 1, at 2-hour intervals on POD 2, and at 4-hour intervals on POD 3–7 by visual examinations or using Doppler ultrasonography [ 45 ]. Reports of flap monitoring using near-infrared spectroscopy (NIRS) in the plastic surgery field have recently been presented [ 46 - 48 ]. The studies reported to date have described NIRS monitoring of flaps used for breast reconstruction.…”
Section: Biosignal Data and Head And Neck Reconstructionmentioning
confidence: 99%